Universal truths and their authority on the truth of the Prophet’s call (Peace be upon him) - Laftah Marouf Laftah Younis, (Islamic Sciences Journal, 2026)
The aim of this research is to examine cosmic phenomena mentioned in Islamic texts that have been confirmed by modern science or realized in reality, supporting the Prophet Muhammad’s (peace be upon him) claim of prophethood. The study highlights the significance of the topic and the reasons for choosing it. The importance of the research lies in its role in strengthening faith in the truth of prophethood through scientific and cosmic evidence referenced by revelation before being discovered by modern science The research consists of three sections: The first defines the proofs of prophethood and their synonyms. The Isra and Mi’raj incident, which included a detailed description of areas the Prophet had not visited. The expansion of the universe, as confirmed by modern scientists, and its mention in the Qur’an before being discovered. This research strengthens the belief that Prophet Muhammad (peace be upon him) is truly sent by Allah and that the revelation he received could only have come from the Creator.